Natural time analysis of the corrected Mexican seismic catalog using complexity measures - Alejandro Ramírez-Rojas; Leonardo Di G Sigalotti; Elsa L Flores-Márquez (Journal of Physics: Complexity)
Natural time analysis (NTA) provides a powerful method to uncover dynamic features hidden behind seismic catalogs and identify when the system enters a critical stage before a major earthquake. In this paper, we perform a NTA of the corrected Mexican seismic catalog, spanning the period from 7 January 2000 to 31 October 2024. The analysis is based on a novel procedure for performing the window selection of events in natural time. In this method, which we term window lengthening , the time series of seismic parameters are calculated by consecutively increasing the length of the initial window by one event so that the last window contains the entire catalog. In this way, the past seismic history is always kept in memory. This procedure reveals that fluctuations of seismic parameters, such as the order parameter of seismicity, the change of entropy under time reversal, and the complexity measure, are less sensitive to low-magnitude events, exhibit deeper and more easily identifiable extrema in the proximity of major earthquakes, and are strongly correlated. These features are desirable to distinguish between precursory and non-precursory fluctuations to strong earthquakes.